CHEST PAIN IN ACUTE CORONARY SYNDROME: CASE STUDY - nining astuti (Jurnal Ilmu Keperawatan Medikal Bedah, 2024)
Acute Coronary Syndrome (ACS) is a global problem and the largest contributor to mortality in the world. The risk of death from ACS increases significantly with aging and delayed management. Complication of ACS that can cause death is Ventricular Septum Rupture (VSR). One of the nursing approaches is the Myra E Levine energy conservation approach which aims to increase the patient's energy conservation. The purpose of this case study is to analyze using Levine's conservation theory on Mrs. MM with a medical diagnosis of ST Elevation Miocard Infact (STEMI) in a comprehensive intensive room. The case study writing method uses a single case design method. The results of the application of case studies with this energy conservation approach obtained tripocognsosis of conservation integrity including decreased cardiac output, impaired gas exchange, risk of infection, impaired electrolyte balance, instability of blood glucose levels and impaired spontaneous ventilation, while for energy conservation integrity is pain and decreased activity tolerance. Interventions focused on acute cardiac care and respiration monitoring. The results of this case study analyzed the nursing diagnosis obtained from the patient. The application of nursing care with Levine's conservation approach can be carried out in various nursing settings both in the critical and terminal phases.